A shapeable, positionable implantable bone repair material and method of making same
Patent Information
- Application Number
- CN202610135445.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2026-01-30
- Publication Date
- 2026-10-09
- Estimated Expiration
- 2046-01-30
AI Technical Summary
但由于人工骨粉均为颗粒状,所以在植入时存在骨颗粒松散、抗压性差以及支撑力有限等问题
(1)材料外层的胶原海绵结构结合了止血材料、骨粉及口腔修复膜的优点,具有高孔隙率,可压缩产生形变,塑形后填入拔牙窝内,材料在吸收血液后恢复形变,与拔牙窝尺寸契合,可达到优良的止血效果并且防止异物进入,起物理屏障的作用,防止牙龈上皮组织长入拔牙窝,为牙槽窝提供骨量及骨密度支持,有利于位点保存。外层的海绵结构还可以防止骨粉颗粒散落,避免对周围组织的刺激和创伤。
Smart Images

Figure CN121846368B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of medical biomaterials technology, and in particular to a malleable and implantable bone repair material and its preparation method, as well as its application in maxillofacial surgery for bone defect repair, dental implant surgery, and periodontal treatment surgery. Background Technology
[0002] The statements herein provide only background information in relation to this invention and do not necessarily constitute prior art.
[0003] Dental implants are a common method of tooth restoration. They involve inserting a dental implant into the jawbone in the area of the missing tooth. After the implant integrates with the surrounding bone, a crown is then attached to restore the missing tooth. However, some patients have insufficient alveolar bone volume or density, which may prevent the implant from settling properly, reducing the success rate of the implant. In such cases, bone grafting surgery becomes a necessary option.
[0004] The main method of bone grafting at present is to fill with artificial bone powder, which is often used in combination with oral repair membranes.
[0005] Artificial bone powder possesses biomechanical properties and structure similar to autologous bone, providing a porous scaffold structure resembling bone, allowing cells to crawl and proliferate. However, because artificial bone powder is granular, it presents challenges during implantation, including loose bone particles, poor compressive strength, and limited support. Furthermore, its granular structure makes it difficult to achieve stable fixation after implantation, requiring the use of a biofilm for coverage. This increases the difficulty of the surgical procedure and may lead to bone powder expulsion, resulting in surgical failure. Summary of the Invention
[0006] To address the shortcomings of existing technologies, the purpose of this invention is to provide a malleable and implantable bone repair material and its preparation method. This material is prepared by encapsulating a gelatin / hydroxyapatite binder with collagen sponge.
[0007] To achieve the above objectives, the present invention is implemented through the following technical solution:
[0008] In a first aspect, the present invention provides a shaped and implantable bone repair material, wherein the interior is a core layer of a composite material of gelatin, gallic acid and hydroxyapatite particles, and the exterior is a porous sponge-like collagen coating layer. The density of the coating layer is 20~100 mg / cm³ 3 The density of the core layer is 100~800 mg / cm³. 3 The particle size of hydroxyapatite is 0.1~2mm.
[0009] The amino groups of gelatin can interact with the phenolic hydroxyl groups of gallic acid to form a viscous matrix that tightly encapsulates hydroxyapatite particles. This solves the problems of looseness and weak binding force in traditional bone powder, improving the mechanical strength and stability of the core material and preventing the displacement or shedding of hydroxyapatite particles. As a natural polymer, gelatin has good biocompatibility and can be gradually degraded and absorbed in vivo, providing space for new bone tissue. The phenolic hydroxyl structure may indirectly assist in hemostasis by promoting platelet aggregation, synergistically with the hemostatic effect of the outer collagen layer.
[0010] Hydroxyapatite, as the core bone repair component, mimics natural bone tissue with its porous structure, providing a scaffold for cell migration, proliferation, and blood vessel ingrowth, ultimately fusing with new bone to achieve bone regeneration. Its granular structure imparts a certain degree of compressive strength, preventing collapse at the bone graft site.
[0011] The high porosity (90%-99%) of the porous, sponge-like collagen coating allows for rapid blood absorption and deformation recovery, ensuring a tight fit with the extraction socket, achieving hemostasis and preventing foreign body intrusion. It also encapsulates the core material, preventing hydroxyapatite particles from scattering and simplifying the surgical procedure. The collagen and gelatin gradually degrade in vivo, releasing hydroxyapatite particles. Their porous structure guides osteoblast colonization and differentiation, ultimately achieving fusion of the material with new bone and improving the success rate of dental implants.
[0012] In some embodiments, the mass ratio of gelatin to gallic acid is 2-20:1; the mass ratio of gelatin to hydroxyapatite is 1-30:70-99.
[0013] For example, the mass ratio of gelatin to gallic acid can be 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, 11:1, 12:1, 13:1, 14:1, 15:1, 16:1, 17:1, 18:1, 19:1, or 20:1. The preferred mass ratio of gelatin to hydroxyapatite is 1:3-9, such as 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, or 1:9.
[0014] In some embodiments, the bone repair material is in the shape of a sheet, block, projectile, frustum, or cylinder.
[0015] In some embodiments, the thickness of the porous sponge-like collagen coating layer is 1-5 mm, and the porosity is 90%-99%.
[0016] Secondly, the present invention provides a method for preparing the shapeable and implantable bone repair material, comprising the following steps: Hydroxyapatite particles were mixed with gelatin and gallic acid in a certain proportion to obtain mixed system A. Mixed system A was poured into a mold, pre-frozen, and then freeze-dried to obtain the core layer precursor. Prepare collagen ultrafine powder solution B, wherein the solid content of B is 1%-5%; The core layer precursor was transferred to another mold, and collagen ultrafine powder solution B was poured in to completely encapsulate the core layer; it was pre-frozen and freeze-dried to obtain the freeze-dried precursor; The lyophilized precursor is cross-linked to obtain the product.
[0017] In some embodiments, the preparation method of mixed system A is as follows: prepare gelatin and gallic acid aqueous solution respectively, mix them evenly, add a certain proportion of hydroxyapatite particles, mix evenly, and the mixture is obtained.
[0018] The concentration of the gelatin aqueous solution is 10%-40% (w / v); preferably 15-30%. For example, it can be 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29%, or 30%.
[0019] The concentration of gallic acid aqueous solution is 0.5%-20%, w / v.
[0020] In some embodiments, the mass ratio of gelatin to gallic acid is 2-20:1.
[0021] The mass ratio of gelatin to hydroxyapatite is 1-30:70-99.
[0022] Preferably, the collagen ultrafine powder solution B has a solid content of 1%-5%, w / w. For example, it can be 1%, 2%, 3%, 4%, or 5%.
[0023] In some embodiments, the pre-freezing temperature is -20 to -40°C, and the pre-freezing time is 4-12 hours.
[0024] The pre-freezing temperature can be -20℃, -25℃, -30℃, -35℃, or -40℃.
[0025] The pre-freezing time can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, or 12h.
[0026] Preferably, the freeze-drying temperature is -5 to -20°C, and the freeze-drying time is 24-72 hours.
[0027] The freeze-drying temperature can be -5℃, -10℃, -15℃, or -20℃.
[0028] The freeze-drying time can be 24h, 30h, 35h, 40h, 45h, 50h, 55h, 60h, 65h, or 70h.
[0029] In some embodiments, after the collagen ultrafine powder solution B completely encapsulates the core layer, the thickness of the collagen ultrafine powder solution B is 1-5 mm.
[0030] In some embodiments, the collagen is derived from bovine hide, bovine Achilles tendon, porcine skin, porcine Achilles tendon, porcine membrane tissue, or porcine pericardium.
[0031] In some embodiments, hydroxyapatite is derived from bovine bone, sheep bone, pig bone, or is artificially synthesized.
[0032] In some embodiments, the crosslinking is vacuum thermal crosslinking or chemical crosslinking.
[0033] Preferably, the crosslinking agent used in the crosslinking process is carbodiimide, hydroxysuccinimide, epoxy compound, diphenyl phosphate, formaldehyde, glyoxylic acid, glutaraldehyde, or genipin.
[0034] The beneficial effects achieved by one or more embodiments of the present invention described above are as follows: (1) The outer collagen sponge structure of the material combines the advantages of hemostatic materials, bone powder, and oral repair membranes. It has high porosity, can be compressed and deformed, and after being shaped, it is filled into the tooth extraction socket. After absorbing blood, the material recovers its shape and fits the size of the tooth extraction socket, which can achieve excellent hemostatic effect and prevent foreign bodies from entering. It acts as a physical barrier to prevent gingival epithelial tissue from growing into the tooth extraction socket, and provides bone volume and bone density support for the alveolar socket, which is conducive to site preservation. The outer sponge structure can also prevent bone powder particles from scattering and avoid irritation and trauma to surrounding tissues.
[0035] (2) The outer layer of the material contains collagen sponge that encapsulates the gelatin / hydroxyapatite composite material. The amino groups of the gelatin in the core layer interact with the phenolic hydroxyl groups of gallic acid, forming a viscous substance that tightly encapsulates the hydroxyapatite particles, thus solving the problem of bone meal or collagen The problems of loose structure, weak bonding, displacement after implantation, and powder shedding in bone powder composite materials can be avoided by preventing bone powder particles from irritating and traumating surrounding tissues, and avoiding bone powder expulsion and collapse of the graft site. During the process of tissue regeneration, collagen and gelatin components are degraded and absorbed, and hydroxyapatite fuses with the new bone to achieve bone regeneration, which can improve the success rate of dental implants.
[0036] (3) Current bone grafting surgery requires high skill from doctors. This material simplifies the operation process for clinicians and makes it easier for them to use. Attached Figure Description
[0037] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an improper limitation of the invention.
[0038] Figure 1 Photograph of the bone repair material prepared in Example 1 of this invention; Figure 2 SEM image of the bone repair material prepared in Example 1 of this invention; Figure 3 Tissue sections (HE stained) of the experimental group at 12 weeks of canine tooth extraction socket restoration experiment of this invention. Caption: □: bone powder; ○: new bone. Figure 4 Tissue section (HE staining) of the control group at 12 weeks of the canine tooth extraction socket repair experiment of this invention. Caption: □: bone powder; ○: new bone. Detailed Implementation
[0039] It should be noted that the following detailed description is illustrative and intended to provide further explanation of the invention. Unless otherwise specified, all technical and scientific terms used in this invention have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.
[0040] The present invention will be further described below with reference to the embodiments.
[0041] Example 1 (1) Add 0.4 g of gallic acid powder (99% purity, Maclean's) to 10 mL of water to obtain a 4% (w / v) gallic acid aqueous solution; dissolve 2.4 g of gelatin (Type A, Sigma) in 10 mL of water and stir in a 60°C water bath until completely dissolved. Mix the two solutions completely to obtain a gelatin / gallic acid mixed system.
[0042] (2) 21.6g of bone repair material (mainly composed of hydroxyapatite particles with a particle size of 0.25~0.5mm, obtained by sieving bovine cancellous bone inorganic salt particles prepared in Example 1 of CN115920135A A bone repair material and its preparation method) was thoroughly mixed with the gelatin / gallic acid mixture system and poured into a mold (cylindrical, inner diameter 8mm, height 15mm). The liquid was pre-frozen at -40℃ for 4h and freeze-dried at -10℃ for 36h; (gelatin: hydroxyapatite = 1:9).
[0043] (3) The method disclosed in the paper "A Decellularized Matrix Wound Material and Its Preparation Method" (Publication No. CN115845116A) was used to prepare porcine membrane tissue decellularized matrix ultrafine powder. Collagen ultrafine powder was emulsified with 1×PBS to obtain an ultrafine powder solution concentration of 3%. (4) Place the gelatin / hydroxyapatite composite material obtained in step (3) into another mold. The mold is equipped with support points to fix the material at a position 2 mm away from the bottom of the mold. The diameter of the mold is 4 mm larger than the diameter of the collagen / hydroxyapatite composite material. Fill the mold with a 3% concentration of ultrafine powder solution to completely wrap it (so that the thickness of the coating layer of the obtained bone repair material is 2 mm). Pre-freeze the material at -40℃ for 4 h and freeze-dry at -10℃ for 36 h. (5) The freeze-dried sample was subjected to vacuum thermal crosslinking at 120°C for 24 hours; (6) After cross-linking is completed, the product is removed for packaging and electron beam sterilization at a dose of 15 kGy; (7) Sample 1 was prepared. A photograph of Sample 1 is shown below. Figure 1 As shown, its SEM image is as follows: Figure 2 As shown.
[0044] Example 2 (1) Add 0.16 g of gallic acid powder (99% purity, Maclean's) to 10 mL of water to obtain a 1.6% (w / v) gallic acid aqueous solution; dissolve 2.4 g of gelatin (Type A, Sigma) in 10 mL of water and stir in a 60°C water bath until completely dissolved. Mix the two solutions completely to obtain a gelatin / gallic acid mixed system.
[0045] (2) 7.2g of bone repair material (mainly composed of hydroxyapatite particles, with a particle size of 0.25~0.5mm, obtained by sieving bovine cancellous bone inorganic salt particles prepared in Example 1 of CN115920135A A Bone Repair Material and Its Preparation Method) was thoroughly mixed with a gelatin / gallic acid mixture, and then poured into a mold (cylindrical, inner diameter 8mm, height 15mm). The mixture was pre-frozen at -40℃ for 4h and freeze-dried at -10℃ for 36h; (gelatin: hydroxyapatite = 1:3) (3) A decellularized matrix wound material and its preparation method (publication number CN115845116A) was used to prepare porcine membrane tissue decellularized matrix ultrafine powder. Collagen ultrafine powder was emulsified with 1×PBS to obtain an ultrafine powder solution concentration of 5%. (4) Place the collagen / hydroxyapatite composite material obtained in step (3) into a mold. The mold is equipped with support points to fix the material at a position 1 mm away from the bottom of the mold. The diameter of the mold is 2 mm larger than the diameter of the collagen / hydroxyapatite composite material. Fill the mold with a 5% concentration of ultrafine powder solution to completely wrap it (so that the thickness of the coating layer of the obtained bone repair material is 1 mm). Pre-freeze the material at -40℃ for 4 h and freeze-dry at -10℃ for 36 h. (5) The freeze-dried sample was chemically cross-linked with 0.5% genipin at 37°C for 12 hours; (6) After cross-linking, the product is packaged and sterilized by Co60 radiation at a dose of 25 kGy; (7) Sample 2 was obtained.
[0046] Comparative Example 1 The difference from Example 1 lies in the change in the content ratio of gelatin to hydroxyapatite. 2.4g of bone repair material (mainly composed of hydroxyapatite particles, particle size 0.25~0.5mm, obtained by sieving bovine cancellous bone inorganic salt particles prepared in Example 1 of CN115920135A, a bone repair material and its preparation method) was thoroughly mixed with a gelatin / gallic acid mixture, with the mass ratio of hydroxyapatite particles to gelatin being 50:50. All other aspects were the same as in Example 1, resulting in Sample 3.
[0047] Comparative Example 2 The difference from Example 1 is that the mold diameter is 0.5 mm larger than that of the gelatin / hydroxyapatite composite material, and a support point is provided in the mold to fix the material at a position 0.5 mm from the bottom of the mold, so that the thickness of the encapsulation layer of the bone repair material is 0.5 mm. Everything else is the same as in Example 1, and sample 4 is obtained.
[0048] Comparative Example 3 The difference from Example 1 is that gallic acid is omitted in step (1), while everything else is the same as in Example 1, and sample 5 is obtained.
[0049] Comparative Example 4 The difference from Example 1 is that in step (1), gallic acid is replaced with gelatin in equal amounts, while everything else is the same as in Example 1, and sample 6 is obtained.
[0050] Comparative Example 5 The difference from Example 1 is that the gelatin / gallic acid mixture was directly mixed with the bone repair material and the ultrafine powder solution. After uniform mixing, the mixture was placed into a mold, and then subjected to subsequent pre-freezing, freeze-drying, and vacuum thermal cross-linking steps. The specific parameters were the same as in Example 1, and sample 7 was obtained.
[0051] Effect verification The samples in the examples and comparative examples were labeled as Sample 1, Sample 2, Sample 3, Sample 4, Sample 5, Sample 6, and Sample 7. Sample 8 was a bone repair material (mainly composed of hydroxyapatite particles, obtained by sieving bovine cancellous bone inorganic salt particles prepared in Example 1 of CN115920135A, a bone repair material and its preparation method), and Sample 9 was collagen. Bone powder composite material (mainly composed of hydroxyapatite particles and collagen, prepared as described in Example 3 of CN111511415A dry implant composition and injectable aqueous implant formulation).
[0052] Product Testing 1. Pressure Deformation Index (1) Test method: Take a sample and measure its height using a general measuring tool, and record it as H1. Place the sample on the sample stage of the compressive strength tester and apply a force of 20N to the sample for 1 minute. Then measure its height again and record it as H2.
[0053] Pressure deformation index = (H1 - H2) / H1 × 100%.
[0054] (2) The test results are shown in Table 1: Table 1 Pressure Deformation Index of Each Sample Group Sample Name Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Sample 7 Sample 8 Sample 9 Pressure deformation index (%) 25.7 32.3 55.2 15.1 44.8 40.4 12.2 / 13.5 The test results show that after pressure was applied to samples 1 and 2, only deformation occurred, and the internal hydroxyapatite was not exposed; samples 3, 5, and 6 showed significant deformation under pressure, indicating poor support strength; after pressure was applied to sample 4, the internal hydroxyapatite was exposed, and a small amount of hydroxyapatite powder fell off; sample 8 was a loose, granular solid, which could not be measured, and it partially broke after pressure was applied; after pressure was applied to samples 7 and 9, some hydroxyapatite powder fell off.
[0055] 2. Porosity (1) Experimental method: CT scans were used to scan samples 1-9 to obtain the original images. The original images were then reconstructed using the 3D reconstruction tool NRecon for selected regions. The selected regions (ROIs) were analyzed using CT Analyser, and the relevant parameters were calculated by the software.
[0056] (2) The test results are shown in Table 2: Table 2 Porosity of each group of samples
[0057] The experimental results showed that the porosity of sample 3 was significantly higher than that of other samples. High porosity is beneficial for blood absorption, but the support strength is poor. The porosity of sample 4 was significantly lower than that of other samples, which is not conducive to the ingrowth of new cells. The porosity of samples 1-2 and 5-9 was relatively moderate.
[0058] 3. Liquid absorbency (1) Test method: Take one sample, weigh it accurately, and record it as m1. Immerse it in a beaker containing water at 20℃±1℃ until it is completely wetted and all air is removed. Take care not to break it. After it has absorbed enough water, record the time for complete water absorption. Use small tweezers to gently hold one corner and take it out of the water. Gently hold the tweezers and drain the water on the surface for 1 minute. Weigh it again and record it as m2. Calculate it according to the following formula.
[0059] The calculation formula is: ; Where: A - water absorption ratio of the sample; m1 - mass of the sample before wetting, g; m2 - mass of the sample after wetting, g.
[0060] (2) The test results are shown in Table 3: Table 3 Liquid absorption factor of each group of samples Sample Name Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Sample 7 Sample 8 Sample 9 Liquid absorbency (times) 3.13 3.05 6.24 1.10 3.01 3.15 3.24 / 1.65 The test results showed that the liquid absorbency of samples 1-3 and 5-7 was significantly higher than that of samples 4 and 9, which was beneficial for blood absorption. Sample 8 was a loose, granular solid and could not be measured.
[0061] 4. In vitro coagulation index test (1) Experimental method: Place a 1 cm thick sample into a petri dish, add 200 μl of preheated 37℃ anticoagulated rabbit blood to the sample surface, then add 20 μl of preheated 37℃ 0.2 mol / L CaCl2 solution, place the petri dish in a constant temperature environment of 37℃, shake at 50 rpm for 5 min, then add 20 ml of ultrapure water, shake at 100 rpm for 5 min in a constant temperature environment of 37℃, collect the uncoagulated red blood cell washing solution, and use an ultraviolet spectrophotometer to measure the absorbance of the test sample washing solution, positive washing solution, and blank washing solution at 540 nm.
[0062] Calculate the in vitro coagulation index (BCI): BCI (%) = (sample absorbance - blank absorbance) / (positive absorbance - blank absorbance) × 100%.
[0063] The lower the BCI value, the better the hemostatic effect of the hemostatic material; conversely, the higher the BCI value, the worse the hemostatic effect.
[0064] (2) The test results are shown in Table 4: Table 4. In vitro coagulation index of each group of samples Sample Name Sample 1 Sample 2 Sample 3 Sample 4 Sample 5 Sample 6 Sample 7 Sample 8 Sample 9 BCI (%) 50.7 59.2 46.7 72.6 49.2 53.3 73.2 86.7 77.5 The test results showed that the BCI values of samples 1-3 and 5-6 were significantly lower than those of samples 4 and 7-9, indicating that the coagulation effect of samples 1-3 and 5-6 was better than that of samples 4 and 7-9.
[0065] 5. Animal tooth extraction socket repair experiment (1) Experimental method: Adult beagle dogs were selected, and tooth extraction models were made. Sample 1 (experimental group) was implanted into the extraction socket and the gingiva was sutured. Sample 8 (control group) was implanted into the extraction socket on the control side, covered with absorbable biofilm, and the gingiva was sutured. The beagle dogs were sacrificed 12 weeks after the operation, and tissue samples from the surgical area and surrounding tissues were taken, fixed, decalcified, and prepared into paraffin sections. The sections were stained with hematoxylin and eosin (HE) and observed under a microscope to observe the bone repair.
[0066] (2) Experimental results: Twelve weeks post-surgery, HE staining results showed that the experimental group ( Figure 3 ) and control group ( Figure 4 In the alveolar bone defect area, bone graft material was found to fill the defect, effectively providing support. Osteoclasts and osteoblasts were observed to proliferate on the surface of the graft material, and osteogenic activity was evident at the defect end within the extraction socket. The experimental and control groups achieved equivalent osteogenic effects, but the experimental group had a simpler procedure, making it more convenient for clinicians.
[0067] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A shapeable and implantable bone repair material, characterized in that: Its interior consists of a core layer of a composite material of gelatin, gallic acid, and hydroxyapatite particles, and its exterior consists of a cross-linked porous sponge-like collagen coating layer; the mass ratio of gelatin to gallic acid is 2-20:1; the mass ratio of gelatin to hydroxyapatite is 1-30:70-99. The density of the coating layer is 20~100 mg / cm³ 3 The density of the core layer is 100~800 mg / cm³. 3 The particle size of hydroxyapatite is 0.1~2mm.
2. The malleable and implantable bone repair material according to claim 1, characterized in that: The mass ratio of gelatin to hydroxyapatite is 1:3-90.
3. The malleable and implantable bone repair material according to claim 1, characterized in that: The bone repair material is in the shape of a sheet, block, bullet, frustum, or cylinder.
4. The malleable and implantable bone repair material according to claim 1, characterized in that: The thickness of the cross-linked porous sponge-like collagen coating is 1~5mm, and the porosity is 90%-99%.
5. A method for preparing the malleable and implantable bone repair material according to any one of claims 1-4, characterized in that: Includes the following steps: Hydroxyapatite particles were mixed with gelatin and gallic acid in a certain proportion to obtain mixed system A. Mixed system A was poured into a mold, pre-frozen, and then freeze-dried to obtain the core layer precursor. Prepare collagen ultrafine powder solution B, wherein the solid content of B is 1%-5%; The core layer precursor is transferred to another mold, and collagen ultrafine powder solution B is poured in to completely encapsulate the core layer. Pre-freezing and freeze-drying yields a freeze-dried precursor. The lyophilized precursor is cross-linked to obtain the product.
6. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: The preparation method of mixed system A is as follows: prepare gelatin and gallic acid aqueous solutions separately, mix them evenly, add a certain proportion of hydroxyapatite particles, mix evenly, and the mixture is obtained.
7. The method for preparing the malleable and implantable bone repair material according to claim 6, characterized in that: In mixed system A, the mass ratio of gelatin to gallic acid is 2-20:
1.
8. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: In collagen ultrafine powder solution B, the solid content is 1%-5%, w / w.
9. The method for preparing the malleable and implantable bone repair material according to claim 6, characterized in that: In mixture system A, the mass ratio of gelatin to hydroxyapatite is 1-30:70-99.
10. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: The pre-freezing temperature is -20~-40℃, and the pre-freezing time is 4-12 hours.
11. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: The freeze-drying temperature is -5 to -20℃, and the freeze-drying time is 24-72 hours.
12. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: After the collagen ultrafine powder solution B completely encapsulates the core layer, the thickness of collagen ultrafine powder solution B is 1-5mm.
13. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: Collagen is derived from cowhide, cow Achilles tendon, pig skin, pig Achilles tendon, pig membrane tissue, or pig pericardium.
14. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: Hydroxyapatite is derived from bovine, sheep, or pig bones.
15. The method for preparing the malleable and implantable bone repair material according to claim 5, characterized in that: The crosslinking is either vacuum thermal crosslinking or chemical crosslinking.
16. The method for preparing the malleable and implantable bone repair material according to claim 15, characterized in that: The crosslinking agents used in the crosslinking process are carbodiimide, hydroxysuccinimide, epoxy compounds, diphenyl phosphate, formaldehyde, glyoxylic acid, glutaraldehyde, or genipin.
Citation Information
Patent Citations
Dried implant composition and injectable aqueous implant formulation
CN111511415A
Acellular matrix wound material and preparation method thereof
CN115845116A
Bone repair material and preparation method thereof
CN115920135A
Composite artificial bone for enhancing osteogenic activity and preparation method thereof
CN103920191A
Bone craft plug with integrated collagen shell and methods thereof
CN110430838A